2020
DOI: 10.3349/ymj.2020.61.5.416
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Fast Healthcare Interoperability Resources-Based 12-Lead Electrocardiogram Mobile Alert System for Suspected Acute Coronary Syndrome

Abstract: Purpose: For patients with time-critical acute coronary syndrome, reporting electrocardiogram (ECG) findings is the most important component of the treatment process. We aimed to develop and validate an automated Fast Healthcare Interoperability Resources (FHIR)-based 12-lead ECG mobile alert system for use in an emergency department (ED). Materials and Methods: An automated FHIR-based 12-lead ECG alert system was developed in the ED of an academic tertiary care hospital. The system was aimed at generating an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Health information interoperability is defined the ability to capture, review, share, and reuse electronic health data seamlessly across health system, thus capture of data is important step to design interoperability framework between healthcare systems [29][30][31]. The preliminary effort to create these three electronic data capture forms is part of a larger program to address the lack of data interoperability between the clinical information systems and clinical registries in field of cardiac EP invasive procedures [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Health information interoperability is defined the ability to capture, review, share, and reuse electronic health data seamlessly across health system, thus capture of data is important step to design interoperability framework between healthcare systems [29][30][31]. The preliminary effort to create these three electronic data capture forms is part of a larger program to address the lack of data interoperability between the clinical information systems and clinical registries in field of cardiac EP invasive procedures [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…1 Cockpit view of the control panel for the Tiantanzhixin app H et al reported that pre-hospital electrocardiography (ECG) transfer using the Wechat app (a popular social media application in China) resulted in earlier reperfusion of ST elevation myocardial infarction patients who were transferred from the non-percutaneous coronary intervention center [55]. Hur S et al observed that the automated Fast Healthcare Interoperability Resources (FHIR)-based 12-lead ECG mobile alert system was successfully implemented in an emergency department, especially for older patients [56]. In a study that enrolled 897 suitable AMI patients, Ben-Assa E, et al demonstrated that telemedicine technology exhibited considerable promise in reducing 30-day readmission rates for post-AMI patients [57].…”
Section: Preliminary Experiences With Using Telemedicine To Manage Stemi Patients At Our Centermentioning
confidence: 99%
“…Condition Management and Treatment (n=15) [12,27,28,30,31,35,36,42,44,45,50,53,54,56,58] CDS Infrastructure (n=7) [15,33,40,41,52,60,63] Lab Result Interpretation --Genomics (n=7) [29,32,46,48,49,58,59] Risk Factor Analysis (n=6) [14,[23][24][25][26]39] Health Metric Monitoring (n=5) [34,37,43,51,61] Lab Result Interpretation --Other (n=3) [38,57,62] HIV Screening (n=1) [55] FHIR n (%) Standards was observational (n=8; 67%), with three studies (25%) reporting CDS needs evaluations. We identified only two studies with randomized components reporting on the use of any of the standards of interest (Curran et al [27] and Kawamoto et al [28]).…”
Section: Topicmentioning
confidence: 99%